Quantum chemical modeling of molecules under pressure. Issue 3 (13th March 2020) - Stauch, Tim
Abstract: Pressure can be used to initiate a plethora of intriguing transformations and chemical reactions. During the past 10 years or so, several quantum chemical methods have been developed that describe the structural and electronic changes in molecules under pressure. This perspective focuses on three of these methods: the extreme pressure polarizable continuum model, the generalized force‐modified potential energy surface, and the hydrostatic compression force field approach. The theoretical background of each method is discussed, and several interesting applications are reviewed. The challenges that the field faces, as well as possible routes for future developments, are pointed out. Abstract : Pressure can be used to initiate chemical reactions. The quantum chemical description of high‐pressure chemistry has emerged as an indispensable tool to understand the complex physico‐chemical effects at play. In this perspective, three quantum chemical tools for application of pressure to molecules, ie, the Extreme Pressure Polarizable Continuum Model (XP‐PCM), the Generalized Force‐Modified Potential Energy Surface (G‐FMPES) and the Hydrostatic Compression Force Field (HCFF) approach, are discussed in terms of theory and applications.